Experiencias de mujeres y el abandono precoz de lactancia Materna. Centro de Salud Cordero Crespo, Guaranda Octubre 2017 – Marzo 2018 - Lozano Cahuana, María Isabel (2018)
With the purpose of describing the experiences of mothers and the early abandonment of breastfeeding in Cordero Crespo Health Center, Guaranda. It is proposed to conduct a case study from a qualitative and quantitative approach in order to answer several questions on issues such as experience with breastfeeding, periodic medical checks, guidance on the importance of breastfeeding, health conditions in the breastfeeding period, time of breastfeeding, casusas of abandonment, among other generalities of this period. Through an in-depth interview prior to a consent of information facility, 40 children under 6 months were determined to date, of which 28 continue with exclusive breast milk and 12 left to breastfeed, with an average age of mothers around 24 years old; being more frequent the abandonment between the fourth and fifth month. They describe their experience with terms such as "pretty, my love is my baby, attachment and trust", they present discrepancies regarding the criteria of body image and free demand found in other studies, especially in societies of greater development and global influence; However, these paradigms have not represented a cause for the early abandonment of this practice. It is necessary to provide nutritional monitoring to children who are not breastfed, specifically in the first semester of life, in order to reduce the likelihood of generating infections due to aseptic measures or poor administration of substitutes. Through a direct follow-up in the period of exclusive breastfeeding through home visits, for a comprehensive education in the home.